Peran Guru dalam Meningkatkan Pendidikan Karakter Siswa di SD Katolik Santo Paulus Tombuluan - Bernadina Waha Labuan; Meri Maria Mula (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2023)
The purpose of this paper is to know the role of the teacher in improving student character education and the inhibiting and supporting factors of the teacher's role in improving student character education and the teacher's efforts in improving student character education. This research uses descriptive research techniques/types with a qualitative approach. Data collection techniques used are observation, interviews and documentation. In this study, the main instrument is the researcher himself. The findings obtained are that the teacher has acted as a facilitator, communicator, motivator and role model as well as being a bridge for students to have good knowledge and character. The main supporting factors are family or parents, the students themselves who have a good personality or character, and the role of the teacher in terms of setting a good example. Inhibiting factors are family or parents who have problems, the environment where they live, and students who have bad personalities or characters. the efforts made by the teacher in improving the character education of students, namely, the teacher seeks to always remind and instill character values to students through the learning process. Apart from that, the teacher also applies it in real actions that can be imitated by students.